AN ANALYSIS OF FRESHMEN ABILITY IN USING COPULAR VERBS - Rinaepi; Rika Septiani; Fovi Sriyuliawati (LPPM STKIP Bina Bangsa Meulaboh, 2023)
This study aims to know how freshmen use the copular verbs and what types of errors occur when they apply them in simple sentences. The writer assumed that paying attention to the learning of copula as the basic English is important because the writer often find that some students still do mistakes in writing simple sentences. This case is also interfered by the background of freshmen. The freshmen learn English just as a foreign language, so there will be many factor will affect this process of learning such as the different system used in these two languages, English and Indonesian as freshmen’s mother tongue. The method of this study use qualitative. The data presented is not by calculation like in the quantitative. The procedure of this research is through asking students to write several simple sentences with suitable pattern. They were asked to use scratch words that they know. Then the researcher collected the data. The next is identifying all those sentences. The writer focuses on how these freshmen use the copular verbs in their sentences. In analyzing the data, the writer specifies the errors analysis into four, those are: 1) collections of sample errors,2) the identification of sample errors, 3)the description of errors, and 4)the explanation of errors (Corder in Eliis, 1996: 48). The result show that there are many errors occur in writing simple sentences. The most frequenly occur is omission. So it can be concluded in teaching English it need to pay attention to grammatical aspect in writing .